From Colonial Port to Post-Revolution: Urban Planning for 21st Century Havana – Photo Essay - Currie, Laura Peñaranda (Consilience, 2012)
Coffee table books are filled with them: the clichés of Havana as “frozen in time”, scented with “nostalgia for a bygone era”. At first sight, the city’s unique combination of urban design and architectural styles suggest a tension between the island’s various historical and political periods. At second glance, the tension lessens into what is a mostly complimentary relationship between patterns, designs, and vision. That is, a city made rich by its combination of continuous innovation and historic preservation. The result is an avant-garde, mostly European (compact, pedestrian, grid-based), urban planning agenda with many assets and challenges to its name. This photo essay aims to: examine how Havana’s colonial history created the city’s basic modern grid street pattern, compact block structure; identify what elements make Havana’s urban character different from that of other major Latin American cities; observe current projects as outlined by the New Master Plan; and, finally identify challenges ahead. By covering these points, the essay sets out to challenge the “frozen in time” perception of Havana by replacing it with one of a unique and historically rich city on the brink of major changes.